Neocolonial Realities of Western Aid in Africa during 21st Century - (:unkn) unknown (My University, 2024)
This article explores the neocolonial dynamics of Western aid to Africa in the 21st century, analyzing its historical origins, contemporary mechanisms, and socio-economic impacts. Despite the formal end of colonial rule, African nations remain entrenched in dependency systems that mirror colonial exploitation. Structural adjustment programs compelled by international financial institutions have exacerbated economic subjugation, undermined sovereignty, and facilitated resource extraction to benefit Western corporations. Western aid often imposes cultural norms and values, weakening indigenous knowledge systems and traditions. Through detailed analyses and case studies of nations such as Congo, Angola, Mozambique, Sudan, and Nigeria, the study identifies recurring patterns of elite capture and systemic corruption that divert aid benefits away from the broader population. In Congo, for instance, resource exploitation has driven persistent conflict and poverty. Angola and Mozambique have faced similar dynamics, with foreign interference fueling civil unrest and resource-driven inequalities. In Sudan, neocolonial pressures have exacerbated internal conflicts and hindered political stability. Nigeria, despite its vast oil wealth, illustrates the paradox of resource abundance coexisting with widespread poverty and infrastructure decay, highlighting the structural deficiencies imposed by neocolonial frameworks. Findings reveal that Western aid mechanisms perpetuate underdevelopment, stifling sustainable growth and local agency while maintaining a dependency cycle. The article decolonized approach to aid, centered on equitable partnerships, African-led development strategies, and transformative practices that prioritize local needs and self-reliance. By addressing these systemic challenges, Africa progress toward sovereignty, inclusivity, and sustainable development beyond the shadow of neocolonialism.
Keywords: African Research